Distinct Impacts of Clinicopathological and Mutational Profiles on Long-Term Survival and Recurrence in Medullary Thyroid Carcinoma - Moon Young Oh; Kyong Yeun Jung; Hoonsung Choi; Young Jun Chai; Sun Wook Cho; Su-jin Kim; Kyu Eun Lee; Eun-Jae Chung; Do Joon Park; Young Joo Park; Han-Kwang Yang (Endocrinology and Metabolism)
Background Medullary thyroid carcinoma (MTC) has a poorer prognosis than differentiated thyroid cancers; however, comprehensive data on the long-term outcomes of MTC remain scarce. This study investigated the extended clinical outcomes of MTC and aimed to identify prognostic factors. Methods Patients diagnosed with MTC between 1980 and 2020 were retrospectively reviewed. Their clinical characteristics, long-term clinical outcomes, and prognostic factors for recurrence and mortality were analyzed. Results The study included 226 patients (144 women, 82 men). The disease-specific survival (DSS) rates for all MTC patients at 5-, 10-, 20-, and 30-year intervals were 92.7%, 89.4%, 74.3%, and 68.1%, respectively. The recurrence-free survival (RFS) rates were 71.1%, 56.1%, 40.2%, and 32.1% at these intervals. DSS was comparable between the groups from 1980–2009 and 2010–2020 (P=0.995); however, the 1980–2009 group had significantly lower RFS rates (P=0.031). The 2010–2020 group exhibited greater extents of surgical and lymph node dissection (P=0.003) and smaller tumors (P=0.003). Multivariate analysis identified extrathyroidal extension as the strongest prognostic factor for both RFS and DSS. Age >55 years and tumor size of ≥2 cm were also significant prognostic factors for DSS, while hereditary disease and lymph node metastasis were significant for RFS. Survival analysis after propensity-score matching of rearranged during transfection (RET)-negative and non-screened RET-positive groups showed comparable DSS but longer RFS in the RET-negative group. Conclusion Extrathyroidal extension was identified as the strongest prognostic factor for RFS and DSS. Older age and larger tumor size were associated with decreased DSS, while RET mutation and lymph node metastasis significantly impacted RFS.